FEATURES OF DOMESTIC INDUSTRIAL ENTERPRISES ENTERING THE FOREIGN MARKET - Zorii , R.I.; Chernobai , L.I.; Lema , H.V.; Mykhailyshyn , L. I . (The actual problems of regional economy development, 2023)
The article analyzes the approaches of domestic and foreign authors regarding the peculiarities of enterprises entering foreign markets. In the scientific works of scientists, there are many studies on the study of the peculiarities of enterprises entering foreign markets. In addition, the authors researched the criteria for choosing foreign regional markets; forms and ways of exit of domestic enterprises to international markets; models and strategies of entering foreign markets. The exit of a domestic industrial enterprise to foreign markets requires a careful action plan. One of the elements of such an action plan is the formation of the process of exit of the domestic enterprise to foreign markets. The authors, with the help of a functional approach, formed the process of the exit of a domestic industrial enterprise to the foreign market. The functional approach involves the application of general management functions: planning, organizing, motivating, controlling and regulating, which are interconnected and provide a step-by-step exit process. In addition, the functional approach ensures the determination of the main factors, both internal (goals, tasks, structure, level of equipment and technology, resources, employees) and external (consumers, suppliers, competitors, trade unions, the state of the economy, infrastructure, international events, international environment, scientific and technical progress, etc.), which will have an impact on the development of the industrial enterprise. Analysis of the above-mentioned factors will contribute to the formation of a SWOT analysis of the exit of domestic industrial enterprises to the foreign market, which will give an opportunity to assess the influence of the strengths and weaknesses of the organization's activities, its opportunities and threats in order to forecast the future state of the activity and its development in the necessary direction. The identification of key opportunities and threats is an important component, as this will precede the identification and minimization of negative features regarding the manufacture of products, performance of works or provision of services, which may lead to the loss of financial resources or consumers.